Enhancing Efficiency of Water Provision - Jasper Dalhuisen; Peter Nijkamp (Tinbergen Institute, 2002)
One of the policy options to increase the efficiency in the provision of scarce water resources is a reduction in transaction costs in water chains by developing integrated forms of water management. Integrated water management in case of river basin areas may comprise inter alia: (1) increasing co-operation at the river basin scale, (2) establishment of a river basin authority for an efficient co-ordination of policy measures in the relevant area, (3) developing a coherent policy addressing the entire water chain, (4) integrated strategies regarding all water functions in relation to other relevant spatial and environmental functions, and (5) 'water-as-ordering-principle', where water functions are the binding constraints for any other competing spatial function in a river basin area.In this paper we discuss the different integrated water management concepts from a theoretical and practical point of view. Moreover, we will explore the potential of efficient integration on the basis of five European projects addressing river basin areas. We argue that the above concepts are from an economic perspective promising, but that external circumstances create barriers for meeting the objectives of integrated water management.
Keywords: Q25; Q28; 330; integrated water management; transaction costs; river basin authorities; Wasserversorgung; Unternehmenskooperation; Transaktionskosten; Welt